Fabrication And Characterization Of Graphene-Based Ink - Satia, Mohd Saidina Dandan (2019)
The main aim of the present study is to develop graphene-based ink with excellent stability, electrical and physical properties for printing electronics by utilizing spray coating and inkjet printing techniques. Firstly, comparison on the different types of graphene-like materials showed that graphene foam (GF) exhibited the highest surface area with the value of 2136 m2g-1. Meanwhile, graphite nanoplatelets (GNPs) and synthetic graphite (SG) displayed highly crystalline structures with the presence of sharp and narrow (002) peak, and high-quality particles with lower ID/IG ratio. Secondly, results showed that viscosity and contact angle of the conductive inks increased significantly with increasing GF, GNPs and SG filler loadings in a polyester varnish (PV) binder. The incorporation of 10 vol.% GNPs improved the electrical conductivity of PV by 186 %, and only 40 % for SG and 10 % for GF at the same filler loading. Next, it is found that GNPs dispersed in ethylene glycol (EG) exhibited better stability with 85 % decrement of the initial concentration after a month, viscosity and wettability than those of propylene glycol (PG) and 2-propanol (IPA). On the other hand, GF dispersed in IPA:EG mixed solvent at ratio of 1:1 showed only 50 % decrement from the initial concentration after a month compared to those of GNPs inks at the same mixed ratio. In the last part, GF/poly(3,4-ethylenedioxythiophene) poly(styrenesulfonate) (PEDOT:PSS) hybrid ink exhibited better stability than GF ink and GF/silver nanoparticles (AgNPs) hybrid ink where the ink showed 30 % decrement from the concentration after a month, 100 % improvement in surface conductivity at 50 printed layers and gauge factor of 4.3. As a conclusion, printed GF/PEDOT:PSS hybrid ink has the potential to be used for strain sensor applications.